2019
DOI: 10.1007/s11205-019-02079-y
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Gender, Wages and Wellbeing: Who Gains and in Which Ways?

Abstract: Empirical studies have consistently documented that while married men tend to lead more prosperous careers after moving, migration tends to be disruptive for careers of married women. We extend this literature by exploring whether migration is followed by a change in subjective wellbeing (SWB). We examine how this experience differs by individuals of different gender, relationship-status and motivations for moving (of both partners in a couple relationship, where relevant). The results are compared to wage dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…There is also some initial evidence that the life satisfaction of emigrants increases when the periods before and after emigration are compared (Erlinghagen et al 2009). This is in line with recent methodically more complex analyses on the development of life satisfaction in the process of internal mobility in Germany (Fuchs-Schündeln and Schündeln 2009; Melzer and Muffels 2012; Erlinghagen et al 2019), in Sweden (Switek 2016), the United Kingdom (Nowok et al 2013;Nowok et al 2018), and Australia (Preston and Grimes 2019). Moreover, compared to people who remained in their home country, life satisfaction of emigrants seems to even increase along with the time they have lived abroad (Erlinghagen 2011;Bartram 2013).…”
Section: Theoretical Considerations and State Of Researchsupporting
confidence: 85%
See 1 more Smart Citation
“…There is also some initial evidence that the life satisfaction of emigrants increases when the periods before and after emigration are compared (Erlinghagen et al 2009). This is in line with recent methodically more complex analyses on the development of life satisfaction in the process of internal mobility in Germany (Fuchs-Schündeln and Schündeln 2009; Melzer and Muffels 2012; Erlinghagen et al 2019), in Sweden (Switek 2016), the United Kingdom (Nowok et al 2013;Nowok et al 2018), and Australia (Preston and Grimes 2019). Moreover, compared to people who remained in their home country, life satisfaction of emigrants seems to even increase along with the time they have lived abroad (Erlinghagen 2011;Bartram 2013).…”
Section: Theoretical Considerations and State Of Researchsupporting
confidence: 85%
“…By contrast, Erlinghagen (2016) found some evidence for a decrease in SWB one to two years before emigration from Germany. Nowok et al (2013), Nowok et al (2018) as well as Preston and Grimes (2019) also find a similar drop in SWB prior to migration for internal moves in Britain and Australia. In that case it seems doubtful whether our quasi-counterfactual comparison with stayers is appropriate because such stayers by definition cannot face any anticipation effect of SWB and thus would not be an adequate reference group.…”
Section: Discussionmentioning
confidence: 68%
“…5 Discussion and conclusions Preston and Grimes (2019), investigating the ex post effects of migration, found that when couples migrate, men's wages tend to rise (while women's wages do not) but it is women who on average gain greater SWB (while men do not). Using the same data, our ex ante results, predicting whether a dual-earner couple migrates, show some similar patterns.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Thus they view migration as a 'path out of unhappiness'. Preston and Grimes (2019) observe that SWB decreases in the year prior to regional migration within Australia for men and women, both for those who are single and for those who are in relationships. They also report that partnered women enjoy a sustained increase in SWB post-migration, while there is no significant increase for their male counterparts.…”
Section: Subjective Wellbeingmentioning
confidence: 85%
“…Migration economists agree that 'economic integration' takes place when immigrants receive the same salary as natives (Borjas, 1990;Amit & Riss, 2014). This integration of immigrants is usually a long-term process, which depends on the number of years of migration (YoM) in the destination country (Preston & Grimes, 2019). YoM is an important consideration because there are time-specific effects of migration (Nowok, Van-Ham, Findlay & Gayle, 2013) like knowing the people, their culture, or language of the host country.…”
Section: Literature Reviewmentioning
confidence: 99%